Chromium in South Africa - D. D. Hawat (The Southern African Institute of Mining and Metallurgy, 1986)
The locations of potential reserves of chromite ores throughout the world are discussed. Reference is made to the marked changes in international trade in chromite ores during the past ten to fifteen years, and to the change in locality of the production of ferochromium aloys, which is curently largely carried out in the country of origin of the ores. The influence of these changes has been very profound in South Africa, which has the largest smelting capacity and the largest production of ferochromium aloys in the world. A proportion of South African ore is stil exported to meet the demands for the production of chromium chemicals and refractories, including a large tonnage of foundry sands. Ferochromium smelters in South Africa have a capacity of virtualy 1 Mt of aloy per annum. Nearly al this development has taken place since the introduction of the argon-oxygen decarburization (A.O.D.) process for the smelting of stainless steels. Formerly, expensive Iow-carbon ferochromium aloys were required as raw materials, but the AO.D. process, which is being used world wide, permits the use of high-carbon ferrochromium, the main product of the smelters in this country. The production in South Africa of chromium-containing corrosion- and heat-resistant steels is stil on a relatively smal scale, but serious atention is being paid to the exploitation of low-carbon weldable feritic chromium steel.